CPS Transformation of Beta-Redexes - Danvy, Olivier; Nielsen, Lasse R. (BRICS Report Series, 2000)
The extra compaction of Sabry and Felleisen's transformation is due to making continuations occur first in CPS terms and classifying more redexes as administrative. We show that the extra compaction is actually independent of the relative positions of values and continuations and furthermore that it is solely due to a context-sensitive transformation of beta-redexes. We stage the more compact CPS transformation into a first-order uncurrying phase and a context-insensitive CPS transformation. We also dene a context-insensitive CPS transformation that is just as compact. This CPS transformation operates in one pass and is dependently typed. Keywords: Continuation-passing style (CPS), Plotkin, Fischer, one-pass CPS transformation, two-level lambda-calculus, generalized reduction.